Implementation of the Revitalized Tertiary Physical Education Program in a Higher Education Institution in Pampanga Grounded on the Statutory Policy of the Commission on Higher Education and UNESCO’s Quality Physical Education Model - Tolentino, Julius Ceazar G.; Sinio, Christian D. (Future Science / FSH-PH Publications, 2024)
The study aimed to evaluate the implementation of the revitalized tertiary physical education program known as the Physical Activity towards Health and Fitness (PATHFit) of a state university in Pampanga, Philippines relative to the statutory standard of the Commission on Higher Education and UNESCO’s Quality Physical Education (QPE) Model. A Mixed Methods Sequential Explanatory Design was utilized involving faculty members (n = 24) and a stratified sample of second-year college students (n = 114). Instrumentations were drafted based on the provisions of two standards considered in the study. The quantitative phase revealed that both the internal stakeholders evaluated the standards of the CMO 39, s. 2021 and the QPE standards and found them to be extremely evident and extremely effective. Additionally, t-tests revealed that there was a significant difference in the evaluation of the respondents. Regression analysis further identified that all five dimensions of the QPE which are assessed in concreteness are significant predictors of program effectiveness. The qualitative phase explored the two dimensions as actualized by the university in terms of notable practices and challenges encountered. It was suggested that the university may institutionalize mechanisms to foster quality physical education standards as embedded in the curriculum development cycle's planning, implementation, monitoring, and evaluation protocols.